Modelling the cost-effectiveness of introducing the RTS,S malaria vaccine relative to scaling up other malaria interventions in sub-Saharan Africa - Winskill, Peter (BMJ Glob Health, 2017)
OBJECTIVES: To evaluate the relative cost-effectiveness of introducing the RTS,S malaria vaccine in sub-Saharan Africa compared with further scale-up of existing interventions. DESIGN: A mathematical modelling and cost-effectiveness study. SETTING: Sub-Saharan Africa. PARTICIPANTS: People of all ages. INTERVENTIONS: The analysis considers the introduction and scale-up of the RTS,S malaria vaccine and the scale-up of long-lasting insecticide-treated bed nets (LLINs), indoor residual spraying (IRS) and seasonal malaria chemoprevention (SMC). MAIN OUTCOME MEASURE: The number of Plasmodium falciparum cases averted in all age groups over a 10-year period. RESULTS: Assuming access to treatment remains constant, increasing coverage of LLINs was consistently the most cost-effective intervention across a range of transmission settings and was found to occur early in the cost-effectiveness scale-up pathway. IRS, RTS,S and SMC entered the cost-effective pathway once LLIN coverage had been maximised. If non-linear production functions are included to capture the cost of reaching very high coverage, the resulting pathways become more complex and result in selection of multiple interventions. CONCLUSIONS: RTS,S was consistently implemented later in the cost-effectiveness pathway than the LLINs, IRS and SMC but was still of value as a fourth intervention in many settings to reduce burden to the levels set out in the international goals.